CONTROL SYSTEM DESIGN OF THE MACHINE PUMP INSPECTION USING PLC-LG GLOFA G7M DR60A IN PT XYZ - Ardi, Syahril; Siamdani, Cokro (Technologic, 2012)
PT XYZ is doing the water pump assembly, require the production process faster. This is because the demands of an ever-increasing production from year to year. In this research, we were carried out pump engine control system design using programmable logic controller inspection type LG-DR60A Glofa G7M. Pump engine inspection serves as a checker engine water pump automatically. Tests on this machine get a faster processing time, which amounted to 15.26 seconds in which previously was 26.65 seconds. The process of machine operation is also very helpful operator and has a safety system for human security. Keywords: pump inspection, programmable logic controller, the system safety